The Dynamics of Arabic Curriculum Transformation In Indonesia (Historical Studies and The Role of Globalization) - septianti, Alya putri; Ridlo, Ubaid; Maswani, Maswani (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2024)
This research examines the changes and development of the Arabic curriculum in Indonesia, especially in the context of historical influences and the impact of globalization. Historically, the Arabic curriculum in Indonesia has undergone various transformations influenced by political, social, and educational policy developments. The role of globalization further accelerates this dynamic by bringing new challenges, such as the need to master communication skills that are more contextual and relevant to the demands of the modern world. This research uses a qualitative approach with a literature study method and historical analysis. The data used is obtained from previous literature sources related to the Arabic curriculum in Indonesia, as well as from current education policies. The purpose of this study is to understand the pattern of Arabic curriculum transformation, the factors that influence it, and how globalization shapes the development of the curriculum in the future. The results show that the transformation of the Arabic curriculum in Indonesia is not only determined by internal dynamics such as local needs, but also by external influences such as global changes in education and technology. This transformation reflects an attempt to answer the challenges of globalization while maintaining existing traditional values.